2014
DOI: 10.1111/cpr.12093
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐125b inhibits cell biological progression of Ewing's sarcoma by suppressing the PI3K/Akt signalling pathway

Abstract: Collectively, these data suggest that miR-125b functions as a tumor suppressor by targeting the PI3K/Akt/mTOR signaling pathway, and may provide potential therapy strategy for ES patients by targeting miRNA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 22 publications
0
57
0
1
Order By: Relevance
“…24,25 EMT is a multistage process that contributes to cancer cells with marked changes in cellular morphology, loss and remodeling of cell-cell and cell-matrix adhesions and gain of migratory and invasive capabilities. 26 In the past years, several signal pathways have been identified that are critical for EMT in cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 EMT is a multistage process that contributes to cancer cells with marked changes in cellular morphology, loss and remodeling of cell-cell and cell-matrix adhesions and gain of migratory and invasive capabilities. 26 In the past years, several signal pathways have been identified that are critical for EMT in cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have already given more prominence to the oncogenic aspects of miR125b, claiming that serum miR-125b could be a novel biomarker for screening human tumors, including non-small-cell lung cancer and breast cancer (Wang et al, 2012;Yuxia et al, 2012). Our previous miR array analysis in ES tissue samples has demonstrated the diagnostic potential of miR-125b (Li et al, 2014). Therefore, it is possible that miR-125b could become a biomarker for the diagnosis of ES.…”
Section: Discussionmentioning
confidence: 93%
“…Another recent study by Li et al showed that restored expression of miR-125b in Ewing's sarcoma cell line A673 markedly suppressed cell proliferation, migration and invasion, arrested cell cycle progression, and stimulated cell apoptosis [63]. They further found that upregulation of miR-125b diminished the expression of PIK3 catalytic subunit delta (PIK3CD), and that inhibition of miR-125b attenuated phospho-AKT activity and retarded the concomitant biologic progression of A673 cells [63]. These results suggest that miR-125b functions as a tumor suppressor by targeting the PI3K/Akt signaling pathway, and in vivo delivery of miR-125b may have a potential therapeutic benefit for OS patients.…”
Section: Phosphatidylinositol-3-kinase (Pi3k)/akt Pathway-related Mirnasmentioning
confidence: 98%
“…Mechanistically, miR-223 can directly target heat shock protein 90B1 (Hsp90B1) and thereby inhibit PI3K/Akt/mTOR signaling [62]. Another recent study by Li et al showed that restored expression of miR-125b in Ewing's sarcoma cell line A673 markedly suppressed cell proliferation, migration and invasion, arrested cell cycle progression, and stimulated cell apoptosis [63]. They further found that upregulation of miR-125b diminished the expression of PIK3 catalytic subunit delta (PIK3CD), and that inhibition of miR-125b attenuated phospho-AKT activity and retarded the concomitant biologic progression of A673 cells [63].…”
Section: Phosphatidylinositol-3-kinase (Pi3k)/akt Pathway-related Mirnasmentioning
confidence: 99%